SEJARAH AL-QUR’AN (Uraian Analitis, Kronologis, dan Naratif tentang Sejarah Kodifikasi Al-Qur’an) - Nur Laila lubis; Raju Alfah Rezi; Ali Akbar (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
In the Muslim view, the Qur'an is a hint of humankind (hudallinnas) that puts the fundamental principles in all the issues of human life. This guide is the foundation of the Islamic religion and serves as a guide for living for its adherents and ensuring the happiness of life both in the world and hereafter. The Qur'an introduces itself to various characteristics and attributes, one of them is that it is a book whose authenticity is guaranteed and always nurtured by God. The history of the Qur'an is so clear and open, since its descent to the present. He was read by Muslims from the past until now. Nevertheless, the Mushaf of the Qur'an that is in our hands until now it has been through a long journey that meandered over a period of more than 1400 years ago and has a long historical background. This paper tries to give an over view of the history of the decline of the Qur'an starts from the exposure of the period of revelation of the Qur'an, the codification of the Qur'an, asbabun nuzul until the effort to dig the values in the gradual decline of the Qur'an.